2013
DOI: 10.1519/jsc.0b013e31828a2c3f
|View full text |Cite
|
Sign up to set email alerts
|

Running Demands and Heart Rate Response in Rugby Union Referees

Abstract: The aim of this study was to examine the match physical demands and exercise intensity associated with men rugby union refereeing using global positioning system technology. Ten male rugby union referees (age, 37.1 ± 5.9 years; body mass, 83.7 ± 4.8 kg; height, 175.5 ± 6.2 cm) were analyzed 2-4 times during a total of 30 national level matches. The average total distance covered by the referees throughout the game was 6,322.2 ± 564.9 m. As a percentage of total distance, 37.3% (2,356.9 ± 291.3 m) was spent wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…There is no connection between general and special physical training at all stages of training (Kurdyukov, 2004, Chopilko, 2014. Little attention is paid to many years of physical training and planning (Di Salvo, 2009;Soloviev, 2018) As a result of theoretical analysis and generalization of unique and scientific and methodological literature (Spirin, 2003;Budogossky, 2008;Kulalaev, 2006;Turbin, 2009;Castagna, 2008;Schenk, et al, 2018;Suarez-Arrones, et al, 2013;Emmonds, et al, 2015;Rebelo, 2011;Webb, 2014;Weston, 2004;2007), it was found out that: ALEXANDER MASLENNIKOV , MIKHAIL SOLOVIEV, LYUDMILA VAKALOVA, DMITRIY ZAIKO,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no connection between general and special physical training at all stages of training (Kurdyukov, 2004, Chopilko, 2014. Little attention is paid to many years of physical training and planning (Di Salvo, 2009;Soloviev, 2018) As a result of theoretical analysis and generalization of unique and scientific and methodological literature (Spirin, 2003;Budogossky, 2008;Kulalaev, 2006;Turbin, 2009;Castagna, 2008;Schenk, et al, 2018;Suarez-Arrones, et al, 2013;Emmonds, et al, 2015;Rebelo, 2011;Webb, 2014;Weston, 2004;2007), it was found out that: ALEXANDER MASLENNIKOV , MIKHAIL SOLOVIEV, LYUDMILA VAKALOVA, DMITRIY ZAIKO,…”
Section: Discussionmentioning
confidence: 99%
“…Numerous experts note that blunders made by referees during refereeing are often associated with a lack of preparedness (Spirin, 2003;Budogossky, 2008;Kulalaev, 2006;Turbin, 2009;Castagna, 2008;Schenk et al, 2018;Suarez-Arrones, et al, 2013;Emmonds, et al, 2015;Rebelo, 2011;Webb, 2014;Weston, 2007). The results show that referees mostly make mistakes in the closing minutes of each half of the game.…”
Section: Introductionmentioning
confidence: 99%
“…Super rugby referees showed no differences in relative distance across each 10min time periods with a match average of 83 ± 5 m•min -1 (Blair et al, 2018) but there was a significant differences (moderate ES) reported in the distance covered, between 21-30 min v 41-50 min (p = .004; d = 1.16), and 31-40 v 41-50 min (p = .022; d = 0.97) (Blair et al, 2018). It is reported that in the first 10 minutes of a match, a rugby referee will experience higher intensities compared with other 10 minute periods (Emmonds, et al 2015;Suarez-Arrones et al, 2013). Spanish/Portuguese referees may be affected by fatigue or the game slows downs as there is a significant difference (p < .05) for the distance covered between the first 10 minutes (876.3 ± 163 m) compared with 50-60 minutes (679.8 ± 117.6 m ), 60-70 minutes (713.03 ± 122.3 m), and 70-80 minutes (694.2 ± 125.7 m) (Suarez-Arrones et al, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…Super rugby referees showed no differences in relative distance across each 10min time periods with a match average of 83 ± 5 m•min -1 (Blair et al, 2018) but there was a significant differences (moderate ES) reported in the distance covered, between 21-30 min v 41-50 min (p = .004; d = 1.16), and 31-40 v 41-50 min (p = .022; d = 0.97) (Blair et al, 2018). It is reported that in the first 10 minutes of a match, a rugby referee will experience higher intensities compared with other 10 minute periods (Emmonds, et al 2015;Suarez-Arrones et al, 2013). Spanish/Portuguese referees may be affected by fatigue or the game slows downs as there is a significant difference (p < .05) for the distance covered between the first 10 minutes (876.3 ± 163 m) compared with 50-60 minutes (679.8 ± 117.6 m ), 60-70 minutes (713.03 ± 122.3 m), and 70-80 minutes (694.2 ± 125.7 m) (Suarez-Arrones et al, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…There are a small number of studies that quantified the movement demands of rugby union referees using Global Positioning Systems (GPS) technology (Blair et al, 2018;Suarez-Arrones et al, 2013). Similar to other invasion team sports, the intermittent nature of rugby union (Cahill et al, 2013) has no definitive endpoint for each passage of play, and the whistle of the referee will dictate the end of each passage of play.…”
Section: Introductionmentioning
confidence: 99%